Validity and Reliability of Critical Thinking Instruments to Measure the Effectiveness of Context-Based Physics E-Module on Wave Materials - Erlina Yusliani Lina; Desnita Desnita (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
Critical thinking skills can be improved through learning physics. Independent teaching materials such as e-modules are needed. Instruments are needed to measure the success of e-module use. This study aims to develop critical thinking skills instrument on physics learning using e- module-based on the context of the material of mechanical waves and stationary waves. The instrument criteria are valid and reliable. The form of the instrument is an essay test that includes five aspects: Interpretation, Analysis, Evaluation, Explanation, and inference. The instrument consists of 18 items. The development model used is ADDIE, with the stages of Analysis, Design, Development, Implementation, and evaluation. The expert validation for each aspect is content 0.84, construct 0.88, and language 0.83 with valid categories. While the results of the empirical validation for five aspects of critical thinking skills are: interpretation three items, analysis three items, evaluation four items, explanation four items, and inference two items are valid. Four items are invalid. These items were discarded. Reliability for critical thinking instrument obtained 0.78 with good category. Referring to the research finding, it can be concluded that the instrument was feasible to use. The impact of this research is the production of a valid and reliable critical thinking instrument, which is used to measure students’ critical thinking skills.